Conveying hope in consultations with patients with life-threatening diseases: the balance between supporting and challenging the patient - Anne Werner; Sissel Steihaug (Taylor & Francis Group, 2017)
Objective: There is limited knowledge about the communication of hope and denial in consultations with patients with life-threatening diseases on a practical level. In this study, we explored a real-life medical consultation between a doctor and a patient with incurable cancer, focusing on conveying hope. Design and methods: We found one consultation especially suited for illustrating how a physician can convey and reinforce hope without attaching it to curative treatment. The consultation was analysed using a method for discourse analysis, where we took as a point of departure that discourse means language in use. Results: The doctor communicated in a recognising manner, expressing respect for the patient as a subject and an authority of his own experiences. The doctor and patient succeeded in creating a good working alliance characterised by warmth and trust. Within this context, there was room for the doctor to challenge the patient's views and communicate disagreement. Conclusions: The doctor succeeds in conveying and maintaining hope. Within a good working alliance with the patient the doctor can convey hope by balancing between supporting and challenging him. Exploring and grasping the patient's real concerns is essential for being able to relieve and comfort him and convey hope.